2000
DOI: 10.1073/pnas.250289597
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant myopathy: Missense mutation (Glu-706 → Lys) in the myosin heavy chain IIa gene

Abstract: We here report on a human myopathy associated with a mutation in a fast myosin heavy chain (MyHC) gene, and also the genetic defect in a hereditary inclusion body myopathy. The disorder has previously been described in a family with an ''autosomal dominant myopathy, with joint contractures, ophthalmoplegia, and rimmed vacuoles.'' Linkage analysis and radiation hybrid mapping showed that the gene locus (Human Genome Map locus name: IBM3) is situated in a 2-Mb region of chromosome 17p13, where also a cluster of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 34 publications
2
103
0
1
Order By: Relevance
“…Not all MYH2 missense mutations are recessive as the c.2116G4A (p.(Glu706Lys)) mutation was reported to cause dominant myopathy. 10 The severity of the myopathy was, however, related to the amount of expressed MyHC IIa in muscle, ranging from clinically mild in childhood and a more pronounced and progressive course with increased CK levels in adults. 18 Inactivation of the genes encoding adult fast skeletal myosin heavy chain IIb and IId/x and creation of MyHC IIx and MyHC IIb null mice have indicated that these genes are required for the normal muscle development and function of adult skeletal muscle in the mouse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not all MYH2 missense mutations are recessive as the c.2116G4A (p.(Glu706Lys)) mutation was reported to cause dominant myopathy. 10 The severity of the myopathy was, however, related to the amount of expressed MyHC IIa in muscle, ranging from clinically mild in childhood and a more pronounced and progressive course with increased CK levels in adults. 18 Inactivation of the genes encoding adult fast skeletal myosin heavy chain IIb and IId/x and creation of MyHC IIx and MyHC IIb null mice have indicated that these genes are required for the normal muscle development and function of adult skeletal muscle in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes were mainly restricted to type 2A fibers, which were either absent or varied in size and showed structural changes. 8,10,18 A later study of patients of three unrelated families with a recessive myopathy, ophthalmoplegia and the absence of type 2A muscle fibers revealed that all patients were compound heterozygous for truncating mutations in MYH2. 11 More recently it was demonstrated that the affected individuals in a large family with recessive myopathy and ophthalmoplegia linked to chromosome 17 p13.1-p12 were homozygous for a frame shift mutation in MYH2 because of a single-base deletion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular genetic studies have identified 3 loci for hIBM: IBM1, IBM2, and IBM3 [5,6,7]. Over the past 10 years, there has been an accumulation of evidence suggesting 4 that IBM1, or desmin-related myopathy (DRM; OMIM #601419), is caused by mutations in the Desmin gene on chromosome 2q35 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The shared genotype and similar phenotypes of DMRV and IBM2 indicates that they are allelic disorders [9,10]. An autosomal dominant type of IBM3 (OMIM #605637), characterized by joint contractures, external ophthalmoplegia, and proximal muscle weakness, results from mutations in the gene encoding myosin heavy chain IIa (MYHC2A or MYH2); this is located on chromosome 17p13.1 [7,11,12]. A recent report that myopathy patients from 3 families carried compound heterozygous mutations in the MYHC2A gene implies that this disorder is inherited via autosomal recessive transmission [12].…”
Section: Introductionmentioning
confidence: 99%